Trend of minimally processed and ultra-processed beverages purchased in Brazilian households: Less milk and much soft drink (2002–2003 to 2017–2018) - Oliveira, Natália; Canella, Daniela Silva (Frontiers in Public Health, 2022)
The consumption of ultra-processed beverages, including sugar-sweetened and artificially sweetened ones, is associated with a number of health problems, which is different considering minimally processed beverages. The objective of this study was to assess the trends in the volume of minimally and ultra-processed beverages purchased for consumption in Brazilian households and their relationship with the proportion of dietary energy derived from ultra-processed foods and beverages. Drawing on data from the nationwide 2002-03, 2008-09 and 2017-18 Household Budget Surveys, the daily volume of beverages purchased per capita (milligrams) was investigated. The minimally processed beverages purchased declined over the period [2002-03: x ̅ 156.5ml (95%CI: 148.3-164.8); 2017-18: x ̅ 101.6ml (95%CI: 98.1-105.1)] and ultra-processed it was stable [2002-03: x ̅ 117.9ml (95%CI: 108.1-127.7); 2017-18: x ̅ 122.8 (95%CI: 111.2-134.4)]. The most purchased beverage in 2002-03 was milk [x ̅: 154.7ml (95%CI: 146.4-162.9)], while in 2017-18 regular soft drinks were the most purchased [x ̅: 110.7ml (95%CI: 99.2-122.2)]. There was a decrease in the purchase of whole and skimmed milk and an increase in the purchase of other ultra-processed beverages between the periods. With the increase in the proportion of ultra-processed foods and beverages in the diet, the volume of ultra-processed beverages purchases rose and minimally processed beverages declined. The monitoring of the beverage consumption and the implementation of public policies, such as taxation on ultra-processed beverages, are essential to promote improvements in health and curbing non-communicable diseases.